Molecular Insights into Oxidative-Stress-Mediated Cardiomyopathy and Potential Therapeutic Strategies - Zhenyu Xiong; Yuanpeng Liao; Zhaoshan Zhang; Zhengdong Wan; Sijia Liang; Jiawei Guo (Biomolecules)
Cardiomyopathies comprise a heterogeneous group of cardiac disorders characterized by structural and functional abnormalities in the absence of significant coronary artery disease, hypertension, valvular disease, or congenital defects. Major subtypes include hypertrophic, dilated, arrhythmogenic, and stress-induced cardiomyopathies. Oxidative stress (OS), resulting from an imbalance between reactive oxygen species (ROS) production and antioxidant defenses, has emerged as a key contributor to the pathogenesis of these conditions. ROS-mediated injury drives inflammation, protease activation, mitochondrial dysfunction, and cardiomyocyte damage, thereby promoting cardiac remodeling and functional decline. Although numerous studies implicate OS in cardiomyopathy progression, the precise molecular mechanisms remain incompletely defined. This review provides an updated synthesis of current findings on OS-related signaling pathways across cardiomyopathy subtypes, emphasizing emerging therapeutic targets within redox-regulatory networks. A deeper understanding of these mechanisms may guide the development of targeted antioxidant strategies to improve clinical outcomes in affected patients.